Relações de gênero e formação docente: masculinidades e posturas feministas no curso de pedagogia da Unifal-MG. - Ribeiro, Diego Duarte (2018)
The present research seeks to reflect how the gender relations are experienced and meaningful by the students of the Pedagogy course of the Universidade Federal de Alfenas - UNIFAL-MG, through the identification of elements that represent the tensions between the practices related to hegemonic masculinity and feminist attitudes. These relationships, present in all moments of life in society, are historical, cultural, economic and political. Thus, femininity and masculinity are human constructions replete with social meaning that relate and manifest themselves through the body. Although each social group has its own way of understanding femininity and masculinity, there are common traits among them, as is the case of female subordination, which does not mean that these relationships are natural, on the contrary, it means that there are social structures that establish a power relationship that values what is connected to the masculine in detriment of what is related to the feminine. Although there is a silence about the participation of women in history, they were not limited to domestic space. They were present in various ways also in the economy, politics and in various sectors of society. Even under tight control, women have always looked for ways to resist. The Western world of the twentieth century witnesses the process of feminist emancipation and the construction of the feminist movement, which, despite being as diverse as the feminine reality, is an instrument of reflection, questioning and transformation of the structures of power that promote the subordination of woman. In addition to the literature review, the following instruments were used to collect data: the Pedagogical Project of the Pedagogy Course, questionnaire, structured interviews and quantitative and qualitative analysis. It was observed that gender relations are silenced in the teacher training process. This silencing contributes to the construction of an essence of what it is to be a woman, which results in the maintenance of practices that value masculinity.